The Arden guide to Renaissance drama an introduction with primary sources - Charry, Brinda (Bloomsbury Arden Shakespeare, 2017)
"This companion to early modern drama equips undergraduate students with the information needed to situate the plays in their socio-political, intellectual and literary contexts. Chapters survey important political, cultural and intellectual events and movements, ranging from the Reformation to emerging nationalism to humanism and to print culture. The book also places at students' disposal some of the key primary documents that constitute the discursive context in which the plays are situated. Finally, it introduces them to the major authors and key dramatic texts of the period and emphasises the importance of both a historicist and close-reading approach to better engage with these works. Rather than using various texts to cover this ground, this book provides undergraduate and college-level students embarking on an in-depth exploration of early modern drama with one resource, making both critical and contextual information accessible even as it helps make their approach to the literature more insightful and sophisticated"-- Provided by publisher.